The Politics of Religion in South Asia: The Impact of Religious Nationalism on India-Pakistan Relations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rise of religious nationalism in South Asia is attributable to the two nation theory which in turn emanates from the communal situation during the British era. This paper traces the roots of religious nationalism in South Asia by referring to the Pre-Partition communal situation in the subcontinent and then by focusing on the development of Islamic fundamentalism in Pakistan and Hindu radicalism in India after the division of the subcontinent. The rise of radical elements in both the countries have been able to effect, quite substantially in Pakistan and in a limited way in India, the view of the people, the state actions and the policies of these two nations towards each other. Thus the aim of the paper is to demonstrate the rise of religious nationalism and its influence on the relationship between India and Pakistan.